Young People As Agents of Sustainable Society : Reclaiming the Future. - Honkatukia, Päivi. (Youth, Young Adulthood and Society Series, 2023)
This book analyses young people's societal participation as a central dimension of their wellbeing, and as vitally important to secure the sustainable future of humankind and the whole eco-social system.